1997
DOI: 10.1097/00005768-199711000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alterations in blood volume on cardiac function during maximal exercise

Abstract: Recently, we proposed that the higher stroke volume (SV) and cardiac output (Q) of endurance-trained (ETR) versus untrained (UTR) individuals are attributable primarily to the enhanced diastolic filling of ETR consequent to a larger blood volume (BV). To test this hypothesis, we examined the effects of manipulating BV on the cardiac function of six ETR and six UTR males. Both groups were examined in the control BV condition (BVctl), then ETR were examined immediately following a 500 mL reduction in BV (BVred) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
124
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 24 publications
14
124
4
Order By: Relevance
“…The SV reached a slight plateau at around 110-130 beats min _1 in both the supine and upright positions, but at maximal exercise there was another rise in SV (predominantly owing to changes in EDV). These findings are similar to those reported for the SV response during upright exercise in male prepubertal distance runners (Rowland et al 1998), endurance-trained men (Gledhill et al 1994;Krip et al 1997;Warburton et al 1999a), endurance-trained women (Wiebe et al 1999) and semi-supine exercise in endurancetrained men (Di Bello et al 1996).…”
Section: Stroke Volume Response To Exercisesupporting
confidence: 86%
See 4 more Smart Citations
“…The SV reached a slight plateau at around 110-130 beats min _1 in both the supine and upright positions, but at maximal exercise there was another rise in SV (predominantly owing to changes in EDV). These findings are similar to those reported for the SV response during upright exercise in male prepubertal distance runners (Rowland et al 1998), endurance-trained men (Gledhill et al 1994;Krip et al 1997;Warburton et al 1999a), endurance-trained women (Wiebe et al 1999) and semi-supine exercise in endurancetrained men (Di Bello et al 1996).…”
Section: Stroke Volume Response To Exercisesupporting
confidence: 86%
“…Several investigators have observed an enhanced diastolic function in endurance-trained athletes, which allows for more complete filling during the later states of vigorous exercise despite a reduction in the diastolic filling time (Gledhill et al 1994;Krip et al 1997;Wiebe et al 1998Wiebe et al , 1999Warburton et al 1999a). In the present investigation, the progressive increases in diastolic filling rate, EDV and SV support the contention that endurance-trained athletes have an enhanced diastolic function that allows them to increasingly use the Frank-Starling mechanism throughout incremental to maximal exercise (Gledhill et al 1994;Krip et al 1997;Wiebe et al 1998Wiebe et al , 1999Warburton et al 1999a).…”
Section: Stroke Volume Response To Exercisesupporting
confidence: 78%
See 3 more Smart Citations